Singular earthen architectural heritage of the Coquimbo Region, Chile: a participatory inventory - Jorquera-Silva, Natalia; Cortez-Godoy, David; Castillo-Ortiz, Rubén; Osorio-Rodríguez, Andrea (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
The earthen architectural heritage from the Colonial and Republican periods has some characteristics in common in the south of the American continent and in Chile, a country where the seismic condition has restricted the volumetric and constructive possibilities of this architecture. However, in the Coquimbo Region, in the north of the country, there are numerous cases of earthen buildings with morphological, constructive and ornamental characteristics that differentiate them from the architectural heritage of the rest of the country, possessing the value of uniqueness. This heritage, located mainly in rural areas, is not characterized or legally protected by its cultural contribution. In this context, a research project was carried out, whose purpose was to record and characterize this unique earthen heritage, combining documentary search, direct observation and information provided by the different rural communities of the región. The results are a series of maps and basic information about the different earthen buildings, which allow the enhancement of this heritage.